Preliminary Investigation into the Periphyton Community of a Tidal Creek, Bonny River, Rivers State, Nigeria (Global Journal of Science Frontier Research, 2018)
In this report the periphyton community of a tidal creek in Bonny River was investigated, study site was demarcated to five stations where samples were collected for six (6) months. Laboratory analysis was based on standard methods and involved identification and enumeration of periphytic organisms. The periphytic community of the study area was composed of 83 species belonging to six classes and 61 genera. The most dominant class was Bacillariophyta represented by 32 species, followed by Chlorophyta with 18 species, Cyanophyta with 17 species, Pyrrophyta 7species, and Euglenophyta and Xanthophyta with 5 and 4 species respectively. The order of total class abundance contrasted with that of species richness, following in decreasing order -Bacillariophyta, Cyanophyta, Euglenophyta, Pyrrophyta, Chlorophyta and Xanthophyta. The increasing presence of Cyanophyta and Euglenaphyta in all stations suggests that study area is under stress which may have been caused by petroleum hydrocarbon.
Keywords: periphyton; cyanobacteria; bio-indicators; species richness; class abundance; dominance